2021
DOI: 10.1155/2021/6636847
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Tai Chi on Balance Function and Exercise Capacity among Stroke Patients: A Meta-Analysis

Abstract: Objective. This study aims to explore the influences of Tai Chi on the balance function and exercise capacity among stroke patients. Methods. Databases including PubMed, Embase, WOS (Web of Science), the Cochrane Library, CNKI (China National Knowledge Infrastructure), Wanfang Data, VIP (VIP database), and CBM (China Biology Medicine disc) were retrieved to gather the figures of randomized controlled trials on the balance function and exercise capacity among stroke patients. Then relevant data were input and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…After removal of duplicates, 82 were excluded at the title and abstract stage. Fifteen articles were retrieved for examination on full text, with 9 reviews [ 21 29 ] finally included. Figure 1 outlines the process of identifying the qualified articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, 82 were excluded at the title and abstract stage. Fifteen articles were retrieved for examination on full text, with 9 reviews [ 21 29 ] finally included. Figure 1 outlines the process of identifying the qualified articles.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published between 2016 and 2021, with 5 [ 21 25 ] written in English and 4 in Chinese [ 26 – 29 ]. Authors of all included reviews were from China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TC is a type of low-affected exercise, which provides a minimal load on the joint muscles. Hence, this exercise is safe for the elderly [11], [12]. The gentle TC movements make the joints and muscles not burdened by excessive pressure [12].…”
Section: Introductionmentioning
confidence: 95%
“…Hence, this exercise is safe for the elderly [11], [12]. The gentle TC movements make the joints and muscles not burdened by excessive pressure [12]. The results of several recent studies have shown that TC was effective for fall prevention and balance control through strengthening lower extremity muscles [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%